Muscle depletion in cirrhotic patients assessed using computed tomography: a cross-sectional study - Romagna, Elisa Sfoggia; Appel-da-Silva, Marcelo Campos; Suwa, Eiji; Maeda, Fabio Kunihiro; Mattos, Angelo Alves de; Tovo, Cristiane Valle (São Paulo Medical Journal, 2020)
BACKGROUND: Sarcopenia is a common complication in patients with cirrhosis and may lead to increased morbidity and mortality. OBJECTIVE: To investigate the prevalence of sarcopenia and its association with disease severity scores, among patients with cirrhosis. DESIGN AND SETTING: Observational and retrospective cohort study carried out in a tertiary-care hospital in southern Brazil. METHODS: This study was conducted among patients with chronic liver disease who were followed up at the gastroenterology and hepatology outpatient clinic of a tertiary-care hospital in southern Brazil and who underwent computed tomography scans of the abdomen through any indication. RESULTS: We included 83 patients in the study. In the population evaluated, there was a predominance of males (57.80%) and the mean age was 56 years. Hepatitis B or C virus was present in the genesis of the disease in 34.9% of the cases, followed by an etiology of alcohol abuse (30.1%). Sarcopenia was diagnosed in 41 (49.4%) of the patients when the cutoff point for cirrhotic patients was used. There was no significant correlation between the Child-Pugh and MELD severity scores and the occurrence of sarcopenia. CONCLUSION: Sarcopenia presents high prevalence among patients with chronic liver disease without any association with predictors of severity.